Effect of inpatient rehabilitation on activities of daily living in pediatric cancer patients in Japan. Issue 2 (June 2018) - Taguchi, Kazue; Ueno, Tomoyuki; Shimizu, Yukiyo; Ishimoto, Ryu; Hada, Yasushi
Abstract : Most pediatric cancer patients decline physical performance therapy, resulting in limitations in the activities of daily living. The objective of this study was to investigate the effects of rehabilitation in pediatric patients with cancer using the functional independence measure (FIM) score. This retrospective study included 25 inpatient children diagnosed with cancer at a single university hospital from January 2016 to December 2016. All patients underwent rehabilitative intervention during their hospital stay. We investigated the contents of the rehabilitation program and the FIM scores before and after the rehabilitative intervention. The average FIM scores improved in all patients; however, only the total-FIM scores (+4.96 points, P =0.009) and motor-FIM scores (+4.04 points, P =0.005) improved significantly. Conversely, cognitive-FIM score did not significantly improve (+0.92 points, P =0.159). In addition, motor-FIM subgroup scores for locomotion (walk/wheelchair and stairs) were significantly higher (+0.36 points, P =0.039 and +0.64 points, P =0.046, respectively) after rehabilitative intervention, regardless of the length of hospital stay. This study showed that FIM score, particularly motor-FIM score and locomotion subgroup scores, significantly improved owing to participation in inpatient rehabilitation. In conclusion, we found that rehabilitative intervention improved physical activity, especially locomotion.